2021
DOI: 10.7196/samj.2021.v111i2.14453
|View full text |Cite
|
Sign up to set email alerts
|

WhatsApp-propriate? A retrospective content analysis of WhatsApp use and potential breaches in confidentiality among a team of doctors at a district hospital, South Africa

Abstract: Confidentiality cannot but be, factually and morally, an all or nothing proposition. (M H Kottow) [1] This open-access article is distributed under Creative Commons licence CC-BY-NC 4.0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…No message contained any patient identifier and in only two cases, the patient’s face was obscured to avoid identification. Notification of consent having been obtained for the WhatsApp consultation was provided only once, similar to a finding reported by Meyer (3 of 109 cases) [ 42 ].…”
Section: Discussionsupporting
confidence: 56%
“…No message contained any patient identifier and in only two cases, the patient’s face was obscured to avoid identification. Notification of consent having been obtained for the WhatsApp consultation was provided only once, similar to a finding reported by Meyer (3 of 109 cases) [ 42 ].…”
Section: Discussionsupporting
confidence: 56%
“…In SSA, many health workers communicate via diverse social media applications such as WhatsApp(inc). (Meyer et al 2021) There is currently no framework in SSA the safe sharing of medical images through these channels. Moreover, most other imaging is still stored in analogue format, such as printed x-rays which are given to the patient and thus not readily accessible or catalogued for long-term monitoring.…”
Section: Data Accessibility Ownership and Privacymentioning
confidence: 99%
“…Our scoping review indicates that WhatsApp has either been used to disseminate survey tools, usually through sharing a link to an online SurveyMonkey or Google Form, or, through the creation of a WhatsApp Group as an intervention to facilitate communication between healthcare workers. We found that while some attention has been paid to the use of WhatsApp in mHealth and telemedicine, and amongst healthcare workers [33][34][35], there is little published that assesses the use of WhatsApp as a data collection tool in health research and communication interventions. Importantly, even within the literature that does exist, limited attention has been paid to the ethical implications of using WhatsApp or the ways in which existing social and economic inequities may affect its use.…”
Section: Whatsapp As a Research Tool For Exploring Migration Mobility Health And Gender In South Africamentioning
confidence: 99%